Kokvigeproduktion baserad på köttraser : en fältstudie - Dahlström, Johanna (SLU/Dept. of Animal Environment and Health (until 231231), 2007)
Most of the beef production in Sweden has been integrated with milk production. Since the 1990:s, the number of dairy cows has decreased. A specialised beef production has developed in purpose to compensate for this decrease. The consumption of beef have increased in the last decade, but the Swedish production has no followed this trend. In 2004, the percentage of beef self-sufficiency in Sweden was 60 %. Sweden was earlier a net exporter but changed during the 1990:s to become a net importer of beef. The import increased dramatically when Sweden joined the EU and the control at the border disappeared.